Cyclic nucleotide regulation of store-operated Ca2+ influx in airway smooth muscle - (:unkn) unknown (AMER PHYSIOLOGICAL SOC, 2006)
Sarcoplasmic reticulum (SR) Ca2+ release and plasma membrane Ca2+ influx are key to intracellular Ca2+ ([Ca2+](i)) regulation in airway smooth muscle (ASM). SR Ca2+ depletion triggers influx via store-operated Ca2+ channels (SOCC) for SR replenishment. Several clinically relevant bronchodilators mediate their effect via cyclic nucleotides (cAMP, cGMP). We examined the effect of cyclic nucleotides on SOCC-mediated Ca2+ influx in enzymatically dissociated porcine ASM cells. SR Ca2+ was depleted by 1 mu M cyclopiazonic acid in 0 extracellular Ca2+ ([Ca2+](i)), nifedipine, and KCl (preventing Ca2+ influx through L-type and SOCC channels). SOCC was then activated by reintroduction of [Ca2+](o) and characterized by several techniques. We examined cAMP effects on SOCC by activating SOCC in the presence of 1 mu M isoproterenol or 100 mu M dibutryl cAMP (cell-permeant cAMP analog), whereas we examined cGMP effects using 1 mu M (Z)-1-[N-(2-aminoethyl)-N-(2-ammonioethyl)amino]diazen-1-ium-1,2- diolate (DETA- NO nitric oxide donor) or 100 mu M 8-bromo-guanosine 3', 5'-cyclic monophosphate (cell-permeant cGMP analog). The role of protein kinases A and G was examined by preexposure to 100 nM KT-5720 and 500 nM KT-5823, respectively. SOCC-mediated Ca2+ influx was dependent on the extent of SR Ca2+ depletion, sensitive to Ni2+ and La3+, but not inhibitors of voltage-gated influx channels. cAMP as well as cGMP potently inhibited Ca2+ influx, predominantly via their respective protein kinases. Additionally, cAMP cross-acti\vation of protein kinase G contributed to SOCC inhibition. These data demonstrate that a Ni2+/La3+ -sensitive Ca2+ influx in ASM triggered by SR Ca2+ depletion is inhibited by cAMP and cGMP via a protein kinase mechanism. Such inhibition may play a role in the bronchodilatory response of ASM to clinically relevant drugs ( e. g., beta-agonists vs. nitric oxide).
Keywords: capacitative calcium entry; trachea; adenosine 3 ',5 '-cyclic monophosphate; guanosine 3 ',5 '-cyclic monophosphate; nitric oxide; isoproterenol; INTRACELLULAR CALCIUM OSCILLATIONS; DEPENDENT PROTEIN-KINASE; RABBIT PORTAL-VEIN; NITRIC-OXIDE; SIGNAL-TRANSDUCTION; CHANNELS; ENTRY; CELLS; TRACHEAL; CGMP